2005
DOI: 10.1089/vbz.2005.5.285
|View full text |Cite
|
Sign up to set email alerts
|

BabesiaDNA Detection in Canine Blood andDermacentor reticulatusTicks in Southwestern Siberia, Russia

Abstract: Babesia infection was studied in 21 blood samples of dogs with symptoms of babesiosis and among 72 Dermacentor reticulatus and 70 Ixodes persulcatus ticks from southwestern Siberia, Russia. Babesia DNA was detected by hemi-nested PCR based on the 18S rRNA gene with subsequent direct sequencing. All of the analyzed canine blood samples and three D. reticulatus, but none from I. persulcatus ticks studied were shown to contain Babesia DNA. Nucleotide sequences of the Babesia 18S rRNA gene fragment of 354 bp long … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
2
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 8 publications
2
25
2
1
Order By: Relevance
“…Similar phenomenon has been observed with TBE virus which is detected in less than 1% of questing I. ricinus (Suss et al, 2004). In a study from Russia (Rar et al, 2005), 4% of D. reticulatus ticks were determined infected with B. canis canis indicating that the infection rate of B. canis in ticks is low but might differ geographically. However, to establish the true infection rate of babesiae, more D. reticulatus ticks from countries across Europe need to be tested.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Similar phenomenon has been observed with TBE virus which is detected in less than 1% of questing I. ricinus (Suss et al, 2004). In a study from Russia (Rar et al, 2005), 4% of D. reticulatus ticks were determined infected with B. canis canis indicating that the infection rate of B. canis in ticks is low but might differ geographically. However, to establish the true infection rate of babesiae, more D. reticulatus ticks from countries across Europe need to be tested.…”
Section: Discussionsupporting
confidence: 71%
“…The vector capacity of D. reticulatus for B. canis is well described and experimentally determined, yet only one study reported the molecular characteristics of B. canis from D. reticulatus ticks (Rar et al, 2005). The aim of our study was to describe B. canis in D. reticulatus collected in Slovakia by using molecular methods, PCR and subsequent sequence analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Although there is a lack of comparable data from similar studies, this is much higher then the prevalence rates (3.6 % and 4.2 %) published by Rar et al (2005a) and Rar et al (2005b) for unfed D. reticulatus. Our sampling method could also contribute to the high proportion of the Babesia-positive ticks, because more Babesia-infected animals (possibly carrying the infected tick) might occur amongst dogs taken to the veterinary clinics than in the average population.…”
Section: Discussioncontrasting
confidence: 56%
“…in Central Europe (Rar et al, 2005;Dautel et al, 2006;Karbowiak, 2009;Mierzejewska et al, 2013;Bajer et al, 2014a,b). The geographical range of D. reticulatus and consequently, of canine babesiosis, has increased alarmingly in Central Europe over the last decade (Sréter et al, 2005;Dautel et al, 2006;Bajer et al, 2014b;Mierzejewska et al, 2014;Jongejan et al, 2015).…”
Section: Introductionmentioning
confidence: 99%